Tracking Hermes, pursuing Mercury - Miller, John F.; Clay, Jenny Strauss (Oxford scholarship online, 2019)
Of all the divinities of classical antiquity, the Greek Hermes (Mercury in his Roman alter ego) is the most versatile and enigmatic. Utilising a multidisciplinary approach, this volume offers an overview of the myriad aspects of this elusive figure, tracking the god's footprints across the many domains in which he partakes.